SOCIAL MEDIA ADDICTION FOR TEENAGERS IN ALGORITHM AND PLATFORM DESIGN: THE LIKE, COMMENT AND SHARE FEATURE - Lovianie, Dona Eka (Universitas Lambung Mangkurat, 2024)
Social media has become an integral part of teenagers' lives, serving as a medium for lifestyle changes and shifts in perspectives, both positively and negatively. This study aims to explore changes in teenagers' communication patterns in the digital era using a qualitative approach and literature study as the data collection method. The findings show that social media significantly influences teenagers' communication patterns in the digital age. The impact can be both positive and negative. Therefore, teenagers need to use social media wisely and responsibly. They need to be aware of its influence on their communication patterns and take steps to minimize its negative effects.